Twin pregnancies conceived by assisted reproduction – Early prediction of preterm birth - Pilić, Igor; Plećaš, Darko; Dotlić, Jelena; Plešinac, Snežana (Vojnosanitetski pregled, 2021)
Background/Aim. Twins conceived by assisted reproduction techniques (ART) are the most susceptible for perinatal complications. The aim of this study was to examine the role of prenatal noninvasive fetal screening of the first and second trimester in prediction of delivery time of ART conceived twins. Methods. Prospective cohort study of all ART conceived twin pregnancies was conducted at the Clinic for Obstetrics and Gynecology, Clinical Center of Serbia, during the period from January 1, 2016 to December 31, 2017. In the 12th gestational week (GW) twins crown-rump lenght (CRL) and thickness nuchal translucency (NT) were measured ultrasonographically. Moreover, serum levels of beta subunit of human chorionic gonadotropin (β hCG) and pregnancy-associated plasma protein A (PAPPA) were assessed. In the 17th GW twins biparietal diameter (BPD), abdominal circumference (AC) and femur length (FL) were determined ultrasonografically. Additionally, β hCG, alpha-fetoprotein (AFP), estriol (E3) and inhibin (INH) were measured in mothers serum. The GW of delivery was noted for each pregnancy. Results. Study included 100 pregnant women with mean age 35.44 ± 5.82. In the examined sample of ART conceived twins significantly more (51%) were delivered in term (≥ 35 GW) (p = 0.001). Delivery time correlated negatively with NT and first trimester β hCG serum levels, while it correlated positively with FL of the smaller twin, second trimester β hCG, AFP and E3 concentrations. According to obtained model for prediction of delivery time in ART conceived twin pregnancies based on first trimester diagnostic tests the significant predictors were PAPPA and β hCG in the 12th GW as well as NT of the first larger twin. Nevertheless, reliability (sensitivity 50%–75%, specificity 30%–40%) of these diagnostic tests was moderate. Conclusion. Prenatal noninvasive fetal screening of the first and second trimester (ultrasonography and laboratory testing) can be used for prediction of delivery time of ART conceived twins.
Keywords: premature births; prognosis; reproductive techniques, assisted; twins; ultrasonography